Necesidad de incorporar regulaciones en la ley orgánica del servicio público respecto de la figura de libre nombramiento y remoción - Armijos Costa, Rosalba Lorena (2014)
At present in our country can be seen as iteratively in public institutions corruption and manipulation that exists with the posts entitled free removal. This is on the understanding that certain features , high level course, must be performed by persons enjoying full confidence of who appoints them and who work closely . It is therefore an extremely risky position, especially in Ecuador, where the political landscape which changes unexpectedly and with amazing frequency, which requires rethinking the relationship between the government and the various parliamentary and extra-parliamentary sectors. Moreover this figure is seen in each of the classes of the public service, that could well be taken as posts easy manipulation and conflict of interest. Given the recent term of meritocracy, then there are only contests merits and opposition to certain posts this without proper control , this figure has a indiscriminate and improper use by public entities without any foundation make certain posts to work under this mode and change names as they go by successive governments, no one truly reflected management for citizenship. But it is also necessary to make a remark to the situation of persons who are appointed under this system, and which are not in employment stability, and 5 thousands of times with his questioned due to the manner of appointment capacity, which contrary evidently constitutionally recognized labor rights. It is therefore necessary that this figure, but is not eliminated, be regulated urgently to curb corruption, influence peddling and enrichment of some people that in view of citizenship sell such charges.